Governance of Change: Portrait of the Al-Mukhtar Cilacap Islamic Boarding School in the Development of Education Quality - Muhammad Yusuf; Ngaftourrohman (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2022)
The intervention of globalization requires Islamic boarding schools always to strive to upgrade institutional capacity and capabilities. In this context, the alternative door for pesantren is to manage institutional changes so they can follow ideal quality standards. This governance allows institutions to dialogue about modernization and the typology of pesantren, which is identical to the traditional style. Al-Mukhtar Adipala Cilacap is a traditional-modern Islamic boarding school trying to find a compatible landscape within the change management framework. This paper attempts to analyze the governance of Al-Mukhtar Adipala's transformation by using a case study approach and borrowing Burnes' theory which is positioned as an analytical knife. This study indicates that: 1) the change choice procedure consists of three interrelated components, namely a SWOT analysis to define the institutional context; provide intentions on the transformation of general knowledge competence and the classical Islamic books; and conduct working meetings to plan and determine strategic policies; 2) the formulation of the strategic policy of the Al-Mukhtar Adipala boarding school consisting of the formulation of a vision and mission, reconstruction of the education system, and periodic evaluations; 3) the operational change formula consists of the input, process, and output of education at the Al-Mukhtar Adipala Islamic boarding school.